Efecto de la tasa de natalidad en la sostenibilidad económica en Ecuador durante 1980 – 2021. - Cuenca Saritama, Vicenta Marilú (2024)
The birth rate in Ecuador has experienced a significant decrease, dropping from 29,97% in 1990 to 17,40% in 2020 (National Institute of Statistics and Censuses, 2021). The aim of this research is to determine the effect of the birth rate on economic sustainability in Ecuador during 1980 – 2021 through the use of econometric techniques, in order to propose policies that promote long-term economic sustainability. Data from the World Bank (2020) and the Global Footprint Network (2021) were used. The methodology employed the Ordinary Least Squares (OLS) model to verify the relationship between the birth rate and economic sustainability, the Vector Autoregressive (VAR) model and the Vector Error Correction Model (VECM) to estimate the long and short-term relationships, and the Granger causality test to show the causal link. Among the results, a progressive decrease in the birth rate attributed to increased education stands out. In the short-term analysis, it is identified that an increase in the birth rate is positively associated with the mortality rate and ecological footprint, furthermore, a negative relationship with economic growth is observed. In the long term, the cointegration analysis shows that the variables move jointly and simultaneously. On the other hand, in the Granger causality, a unidirectional causal link between the birth rate and economic growth has been identified. Given these results, policy implications focus on strengthening comprehensive sexual education policies as a central axis; this strategy seeks not only to regulate the birth rate in response to the identified decrease but also to promote long-term economic sustainability.